Miliary tuberculosis with gastrointestinal involvement in a three-year-old child. Difficulties in the treatment - Ratajczyk-Pekrul, Karolina; Kunka-Mierzwa, Anna; Czerniecka, Barbara; Gonerko, Paweł (Pediatria Polska - Polish Journal of Paediatrics, 2019)
Miliary tuberculosis and gastrointestinal tuberculosis are now rare forms of tuberculosis. We present a case of a nearly three-year-old boy with disseminated tuberculosis with the involvement of lungs, intestines, abdominal lymph nodes, and complicated gastrointestinal obstruction treated surgically. The article presents the difficulties in the diagnostics and treatment of a patient with disseminated tuberculosis and gastrointestinal involvement, i.e. problems with decision-making regarding surgical treatment, difficulties with determining parenteral treatment in a patient with symptoms of gastrointestinal obstruction, identifying indications for systemic corticosteroid treatment, and diagnosis and procedures in immune reconstruction inflammatory syndrome. Additionally, the article presents the clinical picture of miliary tuberculosis in chest X-ray